2018
DOI: 10.1080/1081602x.2018.1500295
|View full text |Cite
|
Sign up to set email alerts
|

Generations, social homogamy and stratification in Finland, 1700–1910

Abstract: This study analyses social heterogamy in western and southern Finland during the early stages of industrialisation, from 1700 to 1910. Marriage patterns are examined by comparing the social classes of spouses' parents, which can be understood as the social origin of the spouse. The rate of heterogamy within the freeholder class was only 19.8%, whereas it was 71.1% in the upper classes, 59.7% in the tenant class and 76.5% in the labour class. In addition, only roughly 20-30% of grooms whose fathers were landown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The finding that educational heterogamy in Tartu correlated with heterogamy by ethnicity or origin is not surprising. Earlier studies have found that the migratory background of individuals is associated with their partner's status origin (Zijdeman and Maas 2010;Roikonen and Häkkinen 2019). Other studies have pointed out that age heterogamy was more likely if one of the spouses was a migrant (Van de Putte et al 2009;Dribe and Stanfors 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that educational heterogamy in Tartu correlated with heterogamy by ethnicity or origin is not surprising. Earlier studies have found that the migratory background of individuals is associated with their partner's status origin (Zijdeman and Maas 2010;Roikonen and Häkkinen 2019). Other studies have pointed out that age heterogamy was more likely if one of the spouses was a migrant (Van de Putte et al 2009;Dribe and Stanfors 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in France, parental status homogamy remained the same during the 19 th century (Maas et al 2011). In some countries, industrialisation may have started a decline in social homogamy among the rural population, but the economic pressure of societal change supported the tendency to protect against resource dilution and thus marry homogamously by social class, as in Norway (Bull 2005) and Finland (Roikonen and Häkkinen 2019). Such somewhat contradictory effects of modernisation are probably expected among rural populations, since they generally had more limited access to education and new occupations than those living in towns.…”
Section: Background and Research Questions 21 Social Heterogamy Durimentioning
confidence: 99%
See 1 more Smart Citation
“…Suomessa 1700-luvun alussa jopa 90 prosenttia tilallisista avioitui toisten tilallisten kanssa, ja 1800-luvun lopullakin osuus oli yli 70 prosenttia. 18 Avioliittoja käytettiin strategisesti perinnönjakojen järjestelemiseen. Tutkituissa kylissä solmittiin lukuisia vastavuoroisia avioliittoja, joissa kahden tilan sisarukset avioituivat keskenään.…”
Section: Sosiaalisen Aseman Säilyttäminen Ja Sukupuolittuneet Mahdoll...unclassified
“…Some authors claim that modernization weakens kin relations and foster migrations, reducing the impact of social and familial influences and leading to a shift in preferences . Modern societies are more likely to record homogamy of achieved characteristics, whereas pre-modern societies tend to show higher levels of ascribed status homogamy (Schwartz, 2013; see also Lippényi et al, 2019;Roikonen & Häkkinen, 2019).…”
Section: Introductionmentioning
confidence: 99%